(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The global practice in healthcare service delivery is to view the patient as a customer whose satisfaction must be given adequate consideration for the mutual benefit of health professionals and the patient. This has made studies on patient satisfaction to be growing worldwide. However, few studies have explored the role of patients’ information seeking behaviour on patient satisfaction. The purpose of the study is therefore to investigate health information behaviour and patient satisfaction in tertiary health institutions in Imo State, Nigeria. This study adopts the descriptive survey research design. The population comprises patients of Imo State Tertiary Health Institutions. A sample of three hundred and seventy-five (375) patients was selected using simple random sampling. A structured questionnaire was used to collect quantitative data which was analysed using both descriptive and inferential statistics. The study found a high level of patient satisfaction among the respondents (Mean= 3.02). it was also found that the overall information seeking behaviour is positive (Mean =3.06). Furthermore, test of hypothesis showed that active information seeking behaviour (R2 = 0.311; p. 0.005)has significant influence on patient satisfaction. The study concluded that it is important for patients and healthcare providers to empower each other through information sharing. It was therefore recommended that tertiary hospitals in Imo state must be more proactive in ensuring that the level of patient satisfaction is sustained with efforts made to ensure that few lapses observed by the patients are addressed.